Effects of tidal operation on pilot-scale horizontal subsurface flow constructed wetland treating sulfate rich wastewater contaminated by chlorinated hydrocarbons - Chen, Zhongbing; Vymazal, Jan; Kuschk, Peter (Environmental science and pollution research international, 2017)
Three different flow regimes were carried out in a pilot-scale horizontal subsurface flow constructed wetland-treating sulfate rich wastewater contaminated with monochlorobenzene (MCB) and perchloroethene (PCE). The three regimes were continuous flow, 7-day cycle discontinuous flow, and 2.5-day cycle discontinuous flow. The results show that intensifying the tidal regime (2.5-day cycle) significantly enhanced MCB removal before 2 m from the inlet and increasing PCE removal efficiency at 0.5 m. The PCE dechlorination process was promoted with tidal operation, especially under the 2.5-day cycle regime, with significant increases of cis-1,2- dichloroethenes (DCEs), vinyl chloride (VC), and ethene, but trans-1,2-DCE was significantly decreased after tidal operation. Due to the high sulfate concentration in the influent, sulfide was observed in pore water up to 20 and 23 mg L-1 under continuous flow and 7-day cycle regime, respectively. However, sulfide concentrations decreased to less than 4 mg L-1 under intensified tidal operation (2.5-day cycle). The increase of oxygen concentration in pore water through intensified tidal operation resulted in better MCB removal performance and the successful inhibition of sulfate reduction. In conclusion, intensifying tidal operation is an effective approach for the treatment of chlorinated hydrocarbons and inhibiting sulfide accumulation in horizontal subsurface flow constructed wetland.
Keywords: Water Purification; Constructed wetland; odpadní voda; mokřady; Biodegradation, Environmental; sírany; čištění vody; Groundwater; Chlorobenzene; Perchloroethene; chlorované uhlovodíky; biodegradace; sulfidy; Wetlands; Pilot Projects; Waste Water; Hydrocarbons, Chlorinated; pilotní projekty; Sulfates; Sulfides; Water Pollutants, Chemical; chemické látky znečišťující vodu; Wastewater; Německo; Germany; Tidal flow